HCI Practices for Building Usable Software. - Moreno, Ana M.; Seffah, Ahmed; Capilla, Rafael; Sánchez-Segura, Maria-Isabel (Computer (00189162), 2013)
The integration of usability engineering methods into software development life cycles is seldom realized in industrial settings.